2019
DOI: 10.1136/bmjopen-2018-026786
|View full text |Cite
|
Sign up to set email alerts
|

How to decide adequately? Qualitative study of GPs’ view on decision-making in self-referred and physician-referred emergency department consultations in Berlin, Germany

Abstract: ObjectivesPatients with acute symptoms present not only to general practitioners (GPs), but also frequently to emergency departments (EDs). Patients’ decision processes leading up to an ED self-referral are complex and supposed to result from a multitude of determinants. While they are key providers in primary care, little is known about GPs’ perception of such patients. This qualitative study explores the GPs’ view regarding motives and competences of patients self-referring to EDs, and also GPs’ rationale fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
1
18
0
1
Order By: Relevance
“…This is in line with previous studies finding [28] that GPs apply the background knowledge of the patient, the patient’s current clinical presentation and the GPs’ personal opinions when deciding whether or not to refer a patient with chest pain [29]. Likewise, a recent study showed that GPs’ considerations for or against providing emergency department referrals went beyond considerations of medical surgery [30].…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with previous studies finding [28] that GPs apply the background knowledge of the patient, the patient’s current clinical presentation and the GPs’ personal opinions when deciding whether or not to refer a patient with chest pain [29]. Likewise, a recent study showed that GPs’ considerations for or against providing emergency department referrals went beyond considerations of medical surgery [30].…”
Section: Discussionsupporting
confidence: 89%
“…EMACROSS consists of a quantitative two-stage survey of respiratory ED patients, an evaluation of secondary hospital data, and a qualitative module [20]. This paper reports the results of the t0 survey and analysis of hospital records.…”
Section: Overview: Research Network and Studymentioning
confidence: 99%
“…Qualitative studies have explored such issues in greater depth [6,9]. Concerning our study, the results of an ancillary GP interview module have been published [20], a paper on the patient perspective is in preparation.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This is in contrast to physician-referral decision-making, associated with referral policies and primary care physicians' belief [25]. More recently, other qualitative studies have reported self-referral motives, including advanced healthcare facilities, health concern and organizational issues [26][27][28] . Our study supporting these ndings and extend patients' negative self-referral motives, including going through the motions and catering to families.…”
Section: Discussionmentioning
confidence: 98%